Enhancement of storage life and maintenance of quality in tomato fruits by preharvest salicylic acid treatment - Baninaiem, Elham; Dastjerdi, Abdolmajid Mirzaalian (Frontiers in Sustainable Food Systems, 2023)
Tomato fruits are usually characterized by a short postharvest life. Their quality decreases during postharvest storage due to losses in nutritional quality and decay. Salicylic acid (SA) has an important role in plant development and response to environmental stress. This research aimed at evaluating the effects of (SA) on fruit quality, extended shelf-life, and ripening of tomatoes (Lycopersicon esculentum cv. Baraka). As a hybrid seed, the “Baraka” cultivar is appropriate for subtropical regions. Three consecutive weeks before harvest, foliar spraying with SA was applied at different concentrations (1, 2, 4 mM). After storage for 10, 20, 30, and 40 days at 10°C, with 85-95% relative humidity (RH), the salicylic acid treatment caused the tomatoes to have lower levels of a* value (redness), decay, electrolyte leakage and chilling injury. These features were associated with higher levels of ﬁrmness, titratable acidity, vitamin C, and ascorbate peroxidase content, compared to the control. The results indicated that 4 mM SA was most effective in maintaining quality of fruit, whereas 1 mM SA was least effective. In sum, SA can be considered a potent treatment that can effectively control postharvest loss.